Life Cycle Cost Analysis to Maintain Material Construction on Hotel Development Project Batu - I Kadek Adit Putra Igmas; Yatnanta Padma Devia; Kartika Puspa Negara (Rekayasa Sipil, 2023)
Life cycle cost analysis is a crucial design process in controlling the initial costs and future costs of owning a company investment project. Therefore, it is necessary to conduct a life cycle analysis study cost to find out what cost categories are contained in the Project hotel development in the Batu City area also, see how much the total cost incurred by a project. The construction of the hotel starts from the design stage to the technical age of the hotel that has been completed set. The purpose of this study is to identify service life components hotel building materials, and make a long-term plan for the life cycle cost of the hotel building in the Batu City area. The results of this study indicate that in the Life Cycle Cost Analysis using the essential cost of building investment for 15 years, where there are items of Initial Cost, Annual Recurring Cost, Non-Recurring Cost, the LCC cost of Architectural Work on the Initial Design is IDR 21,542,108,279.